The Place of Ultrasonography in the Evaluation of Rib Fractures - Fulya Bakılan; Gökhan Yüce; Ahmet Çağdaş Biçen; Tanju Keten (Galenos Yayinevi, 2015)
Objective: The aim of this study was to investigate whether ultrasonography is superior to chest x-ray in detecting rib fractures in patients with minor blunt chest trauma and chest pain. Materials and Methods: Ultrasonography findings of 32 patients with minor blunt chest trauma showing no evidence of a rib fracture on anteroposterior chest x-rays, were documented. Presence of cortical discontinuities, acoustic shadows, reverberation artifacts, and hematoma by ultrasonography was proposed as the diagnostic criteria for detecting the rib fracture. Results: Rib fracture was detected in 20 patients (62.5%) according to ultrasonography results. A mildly displaced fracture was detected in 7 patients (35%), hematoma was detected in 3 patients (15%) and multiple fractures (in 5th, 6th, 7th, and 8th ribs) were detected in 1 patient (5%). Conclusion: The results of our study showed that ultrasonography is superior to chest x-ray, in detecting rib fractures.